Prognosis of Benign Congenital Hypotonia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
Twenty five children diagnosed with benign congenital hypotonia (BCH) between infancy and 2 years of age were examined at 6 to 8 years of age and compared to 26 controls, matched for sex, age, and weight, in a study at the School of Occupational Therapy, Hebrew University-Hadassah Medical School, and Child Development Institute, Jerusalem.